Penerapan Model Cooperative Learning Tipe Numbered Heads Together (NHT) untuk Meningkatkan Hasil Belajar Fisika Siswa SMA Negeri 1 Bolano - Andi Sumadi; Yusuf Kendek; Mumammad Jarnawi (Universitas Tadulako, 2021)
The study aimed to determine the improvement of learning outcomes by implementing the cooperative learning model type Numbered Heads Together (NHT) of students in class XI IPA SMA Negeri 1 Bolano. This research was action research carried out cyclically and refers to the research design of the Kemmis & Mc. Taggart. This research had four stages, planning, implementing actions, observing, and reflecting. The types of data obtained were qualitative and quantitative data. Qualitative data was obtained from teaching and learning activities in the form of observations. Quantitative data were learning outcomes obtained by tests. Learning outcomes of the cycle I got classical learning completeness of 21.21%, classical absorption of 55.95%, teacher activity was in the sufficient category with a percentage of 73.52%, and student activity was in the sufficient category at a percentage of the cycle of 75%. Cycle II obtained classical learning completeness of 90.90%, classical absorption 80%, teacher activity was in the very good category with a percentage of 91.67%, and student activity was in the very good category at a percentage of 92.77%. Based on the performance indicators, the conclusion is that implementing the Numbered Heads Together (NHT) cooperative learning model can improve student learning outcomes of students in class XI IPA SMA Negeri 1 Bolano.